Honey & Co. : the cookbook - Packer, Sarit; Srulovich, Itamar (Little, Brown and Company, 2015)
Offers a selection of accessible Middle Eastern recipes from the restaurateurs, including spreads and dips, salads, one-pan dishes, soups, Persian entrées, tagines of North Africa, sofritos of Jerusalem, and stews of Iran.